Farmers’ perception of the role of veterinary surgeons in vaccination strategies on British dairy farms - Richens, I.F.; Hobson-West, Pru; Brennan, Marnie L.; Lowton, R.; Kaler, Jasmeet; Wapenaar, Wendela (BMJ Publishing Group, 2015)
There is limited research investigating the motivators and barriers to vaccinating dairy cattle. Veterinary surgeons have been identified as important sources of information for farmers making vaccination and disease control decisions, as well as being farmers’ preferred vaccine suppliers. Vets’ perception of their own role and communication style can be at odds with farmers’ reported preferences. The objective of this study was to investigate how dairy farmers perceived the role of vets in implementing vaccination strategies on their farm. Semi-structured interviews were conducted with 24 dairy farmers from across Britain. The data were analysed using thematic analysis. Analysis revealed that farmers perceive vets to have an important role in facilitating decision-making in all aspects of vaccination, including the aspects of vaccine distribution and advice on implementation. This important role is acknowledged by farmers who have regular veterinary contact, but also farmers with solely emergency veterinary contact. Given this finding, future work should investigate the attitudes of vets towards vaccination and how they perceive their role. Combining this knowledge will enable optimisation of vaccination strategies on British dairy farms.